Biotechnology in animal agriculture and poverty alleviation: An NGO perspective - Bayer, W.; Wanyama, J. (TSAP and ILRI, 2006)
Biotechnology has only limited potential to alleviate poverty in rural Africa because it does not address the main reasons for poverty such as weak infrastructure, bad governance and unfavourable terms of trade. Looking at the main characteristics of the predominantly small-scale animal farming in Africa, the potentials and limitations for biotechnological applications in food processing, forage improvement, animal breeding and animal health are discussed. Indigenous biotechnology under the control of livestock farmers can be beneficial, whereas—with the exception of some animal health technologies—large-scale and ‘high-tech’ applications of biotechnology have shown little potential to alleviate poverty. Indeed, these applications can have the opposite effect. Rather than pouring an undue amount of human and financial resources into further refinement of advanced biotechnology, African livestock researchers should develop their own research agenda that addresses the real problems of small-scale livestock keepers and poverty alleviation.